2022
DOI: 10.3389/fpubh.2022.926465
|View full text |Cite
|
Sign up to set email alerts
|

Building community capacity to stimulate physical activity and dietary behavior in Dutch secondary schools: Evaluation of the FLASH intervention using the REAIM framework

Abstract: BackgroundBuilding community capacity in secondary schools is a promising strategy for the sustainable implementation of school-based health promotion. The Fit Lifestyle at School and at Home (FLASH) intervention explored how building community capacity works for the prevention of overweight following four strategies: leadership, participatory school culture, tailored health-promotion activities, and local networks. This study evaluates the intervention's impact on community capacity and capacity-building proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 46 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…The importance of identifying and empowering organisation champions to successfully scale up public health interventions has been described previously in other comparable research within and beyond the school-setting (Carson et al. , 2014; van Dongen et al. , 2022; Lane et al.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The importance of identifying and empowering organisation champions to successfully scale up public health interventions has been described previously in other comparable research within and beyond the school-setting (Carson et al. , 2014; van Dongen et al. , 2022; Lane et al.…”
Section: Discussionmentioning
confidence: 85%
“…However, in many schools, enthusiasm about the project was less than anticipated and limited time and/or efforts were spent on involving relevant stakeholders. Given the importance of stakeholder involvement for sustainable implementation (Bartelink et al, 2019a, b, c;Deschesnes et al, 2003;Durlak and DuPre, 2008;Pearson et al, 2015), for future projects it is crucial to provide schools with more extensive guidance and support on how to adequately do this (van Dongen et al, 2022). A process coordinator could play a more Healthpromoting activities in school context proactive role in this, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study evaluated the impact of FLASH on these capacity-building strategies ( van Dongen et al ., 2022 ); it revealed that the level of community capacity increased in all participating schools. Most notable improvements were seen in leadership.…”
Section: Introductionmentioning
confidence: 99%
“…The Healthy School approach, the Dutch version of the HPS framework, was used as a starting point for the intervention schools because they were already familiar with this approach at the start of the FLASH intervention and would continue with it after FLASH [78,81]. A previous study evaluated the impact of the FLASH intervention on community capacity and capacity-building processes [173]; it revealed that the level of community capacity increased in all participating schools. Most notable improvements were seen in leadership.…”
mentioning
confidence: 99%